The Influence of Audit Quality in Controlling Practice Earnings Management - Pinem, M Rizky Arbi; Sihombing, Geraldo; Sidabutar, Fhilvino (Asosiasi Dosen Akuntansi Indonesia, 2023)
The purpose of this research is to determine the effect of audit quality in controlling earnings management practices. This research uses qualitative research with the literature review method as the methodology. The research will use literature study data analysis and the results obtained show that the influence of audit quality in controlling earnings management practices in a corporate entity. It is hoped that the results of this research will provide insight into the understanding of the important role of audit quality and earnings management. The aim of studying the influence of audit quality on controlling earnings management activities is to evaluate the extent of the role of audit quality in preventing, detecting or minimizing the results of management activities in the business environment. This research may include evaluating the accuracy, completeness and integrity of the audit as well as its impact on the integrity of the financial information the company presents to its stakeholders.